2013
DOI: 10.1016/j.cellimm.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoke extract on primary activated T cells

Abstract: Tobacco smoking predisposes the development of diseases characterized by chronic inflammation and T cell dysfunction. In this study, we aimed to determine the direct effects of cigarette smoke on primary T cells and to identify the corresponding molecular mediators. Activated T cells cultured in the presence of cigarette smoke extract (CSE) displayed a dose-dependent decrease in cell proliferation, which associated with the induction of cellular apoptosis. T cell apoptosis by CSE was independent of caspases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 39 publications
3
32
0
1
Order By: Relevance
“…The mechanisms involved in NTHi colonizing the lower airways and becoming pathogenic are not well understood but could potentially be due to impaired T-cell responses as a result of cigarette smoke-induced damage. [53][54][55] Previously, we have shown that cytotoxic T cells are dysregulated in the lungs of patients with COPD by means of aberrant regulation of the programmed cell death protein 1 signaling pathway, and this might be a mechanism through which T cells contribute to excessive inflammation in response to respiratory pathogens. 42 Future work is needed to understand the mechanisms controlling T-cell activation and how these become impaired in diseases associated with chronic NTHi colonization.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in NTHi colonizing the lower airways and becoming pathogenic are not well understood but could potentially be due to impaired T-cell responses as a result of cigarette smoke-induced damage. [53][54][55] Previously, we have shown that cytotoxic T cells are dysregulated in the lungs of patients with COPD by means of aberrant regulation of the programmed cell death protein 1 signaling pathway, and this might be a mechanism through which T cells contribute to excessive inflammation in response to respiratory pathogens. 42 Future work is needed to understand the mechanisms controlling T-cell activation and how these become impaired in diseases associated with chronic NTHi colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, exposure to cigarette smoke results in increased susceptibility to infections and major changes in cellular immune responses, promoting chronic inflammation and immune dysfunction. [15][16][17] Because this study used a retrospective design, data on smoking history were collected from medical records. Therefore, there might be a retrospective deviation in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were observed in smokers and in animals exposed to CS [116][117][118]. Several studies described the implications of CS for different immune cell types, as well as the diverse actions of nicotine or CS, depending on the pathological environment, for example, UC or CD, in which the immune cells originated [77,99,112,[119][120][121][122].…”
Section: Immune Regulationmentioning
confidence: 55%